Arca Perwujudan Di Pura Puseh Penataran Desa Adat Kabetan, Gianyar (Kajian Tentang Sejarah, Fungsi Dan Implementasinya Sebagai Sumber Belajar Sejarah) - Nama, Ida Bagus Putu Adi; Purnawati, Desak Made Oka; Yasa, I Wayan Putra (Widya Winayata : Jurnal Pendidikan Sejarah, 2025)
The purpose of this study is to explore the historical existence of embodiment statues at Pura Puseh Penataran, Desa Adat Kabetan, Bakbakan, Gianyar. It aims to examine the function and meaning of these embodiment statues in the context of modern society and to implement history learning by utilizing these statues as learning resources at vocational high schools (SMK). This research employs a qualitative method with several stages: determining the research location, selecting informants, data collection techniques (observation, interviews, document studies), data authenticity validation techniques (data triangulation, method triangulation), and data analysis techniques. The findings reveal that the embodiment statues at Pura Puseh Penataran reflect the development of religious culture in Bali from the 13th to the 14th century AD. These statues serve religious rituals, cultural symbolism, educational media, and academic studies, with evolving meanings as a cultural heritage. The implementation of history learning in Phase E through Project-Based Learning (PjBL) enhances historical understanding, critical thinking, and appreciation of cultural heritage. Keywords: embodiment statues, function, and implementation